The Gender Effect in Student Selection of Professors for Classes. Issue 1 (2nd January 2018) - Mendez, Jeanette Morehouse; Mendez, Jesse Perez
Abstract : The purpose of this study is to examine gender preferences that students may have in hypothetical professor selection by either profile picture or catalog listing. First, we showed picture profiles of male and female professors (while controlling for attractiveness and age) to student participants and asked them to select one or the other. Second, we provided students with faculty names indicating their gender in a simulated course catalog format and asked them to select one from the pair. We found that students preferred male faculty overall, both in the photo and name experiment. When we compared male students to female students, male faculty were consistently selected in the name experiment; however in the photo experiment, female students preferred female faculty while male students preferred male faculty. Further, we found evidence of indirect racial effects. Students more often selected male faculty when the photos were White and when the names were White, Black, and Asian. Hispanic faculty pairings were the only ethnic groups where female faculty were preferred over male faculty.